The Cooperative Approach in Managing Safety Issues for Halal Industrial Parks in Malaysia: Embracing Opportunity - Azizan, Ramli; Mazlin, Mokhtar; Badhrulhisham, Abdul Aziz; Nor Azman, Ngah (Inderscience Publishers, 2014)
The progressive development of Halal Industrial Park is to realise Malaysia's aspiration to become a global Halal hub champion. The purpose of this paper is to provide an initial framework linking the literature on how cooperative approach would bring improvement to the safety management performance at Malaysia's Halal Park. The cooperative approach such as industrial symbiosis is synonymously linked to material and energy exchange. Thus, we explored other potential cooperation which has been paid less attention–the cooperative safety management, and the rationale of this study from Islamic perspective was also discussed. Moreover, we have also interviewed a few industrial safety experts and most of them agreed that this initiative is noteworthy especially in the context of Malaysia's industrial park. In the end, we proposed the development of future research framework whereby an intensive and in–depth study is required since the establishment of the Halal Park is still in its infant stage.